Lines of best fit for the zeros and for the critical points of a polynomial - Keady, Grant (American Mathematical Society, 2011)
Combining results presented in two papers in this MONTHLY yields the following elementary result. Any line of best fit for the zeros of a polynomial is a line of best fit for its critical points